Chemical Signatures of New Pesticides in the Bovine and Caprine Milk Samples Collected from Western Uttar Pradesh (India) - Rana, Suresh V. S.; Verma, Yeshvandra; Rathi, Uday Veer; Vashistha, Lalit Mohan (Journal of Ecophysiology and Occupational Health, 2021)
Raw buffalo, cow and goat milk collected from different locations of Northern India has been analyzed for suspected pesticides viz. azimsulfuron, cypermethrin, thiabendazole, crotonolactone, fluoxastrobin, aldicarb and carbofuran. Buffalo milk tested positive for azimsulfuron (4.51 ng/ml), cypermethrin (7.21 ng/ml) and thiabendazole (4.57 ng/ml). Cow's milk did not show the presence of cypermethrin and thiabendazole, however, azimsulfuron (0.86 ng/ml), crotonolactone (4.73 ng/ml) and fluoxastrobin (0.54 ng/ml) were determined. Milk of the goats registered the presence of carbafuron (7.69 ng/ ml), fluoxastrobin (5.41 ng/ml) and azimsulfuron (5.28 ng/ml). Since all the milching cattle are herbivorous, these pesticides entered animal through food chain. The consumption of milk containing these pesticides even in traces may be hazardous to human population of Northern India. Concurrent presence of these pesticides may be more hazardous due to their synergistic manifestations. New synthetic molecules like azimsulfuron, fluoxastrobin and crotonolactone may pose severe public health problems.